Bisection Method and Falsi Regulation Method to Determine The Roots of Polynomial Equations - Melki Imamastri Puling Tang (Program Studi Matematika Universitas Sulawesi Barat, 2023)
Some simple polynomial equations can be solved by the remainder theorem, so there is no need for numerical methods to solve them, because the roots of equations are very easy to do using analytical methods, while there are some polynomial equations that are difficult and complex to find roots using analytical methods. In this literature review, researchers will use the bisection method and the false rule to find the roots of polynomial equations. Based on the steps or sequence of calculation of the polynomial roots of , using the bisection method, the author states that from the first step to the eleventh step, if the calculation continues then in the second step f(a)*f(c)>0 or away from zero as shown in table 1 above. The author states that if the twelfth step continues, then f(a)*f(c) will approach zero and it can be seen that there are looping process approaches resulting from f(a)*f(c). This research study concludes that the roots of the polynomial of , using the bisection method are 1.36474675. Based on the steps or sequence of calculating the roots of the polynomial of on, using the false position method (false rule), the author states that from the first step to the 366th step it turns out that f(c)=0.003195 when c=1,365423447. Thus the polynomial roots of using the false position method (regulation false) are 1.365423447. Keywords: Roots of polynomial equations.